Assessing kinetic and epitopic diversity across orthogonal monoclonal antibody generation platforms. Issue 2 (17th February 2016) - Abdiche, Yasmina Noubia; Harriman, Rian; Deng, Xiaodi; Yeung, Yik Andy; Miles, Adam; Morishige, Winse; Boustany, Leila; Zhu, Lei; Izquierdo, Shelley Mettler; Harriman, William
ABSTRACT: The ability of monoclonal antibodies (mAbs) to target specific antigens with high precision has led to an increasing demand to generate them for therapeutic use in many disease areas. Historically, the discovery of therapeutic mAbs has relied upon the immunization of mammals and various in vitro display technologies. While the routine immunization of rodents yields clones that are stable in serum and have been selected against vast arrays of endogenous, non-target self-antigens, it is often difficult to obtain species cross-reactive mAbs owing to the generally high sequence similarity shared across human antigens and their mammalian orthologs. In vitro display technologies bypass this limitation, but lack an in vivo screening mechanism, and thus may potentially generate mAbs with undesirable binding specificity and stability issues. Chicken immunization is emerging as an attractive mAb discovery method because it combines the benefits of both in vivo and in vitro display methods. Since chickens are phylogenetically separated from mammals, their proteins share less sequence homology with those of humans, so human proteins are often immunogenic and can readily elicit rodent cross-reactive clones, which are necessary for in vivo proof of mechanism studies. Here, we compare the binding characteristics of mAbs isolated from chicken immunization, mouse immunization, and phage display of human antibody libraries. Our results show that chicken-derived mAbs not only recapitulate the kinetic diversity of mAbs sourced from other methods, but appear to offer an expanded repertoire of epitopes. Further, chicken-derived mAbs can bind their native serum antigen with very high affinity, highlighting their therapeutic potential.